Modelo Conceitual de Serviço de Recomendações para TV 3.0 - Poggy, Arthur; Borges, Paulo Victor; Moraes, Daniel de Sousa; Colcher, Sérgio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
The evolution toward TV 3.0 establishes a hybrid broadcast–broadband ecosystem, application-oriented and characterized by new requirements for personalization and interoperability. Although recommender systems are widely explored on OTT platforms, their use in the television context still faces specific challenges, such as limited interaction, shared viewing, and constraints on data collection. This work proposes a conceptual model for a recommendation service based on multiple specialized agents coordinated by a central orchestrator. The proposal aims to provide a minimum viable abstraction, modular, extensible, and aligned with the constraints of the television environment. In addition to detailing the architecture, we present a hypothetical use case that illustrates the end-to-end flow and discuss implications for transparency, explainability, and governance of recommendations. The results are intended to support the adoption of personalization mechanisms in TV 3.0, reconciling technological innovation with requirements for reliability and usability.